Political and Contemplative Life in Aristotle’s Account of Happiness - Candiotto, Laura (Peitho. Examina Antiqua, 2012)
Through the concepts of ἔργον and βίος, the article describes the two happiest forms of life, i.e., the theoretical and the political one, asking whether happiness is founded on the conjunction of the two. Focusing on the connection between philosophy, education and politics the paper emphasizes the role of contemplation as πράξις and the importance of philosopher for the city.